Konsep Dasar Manajemen Sumber Daya Manusia Pendidikan Islam di MDTA Sukma Illahi Canduang - Alhamda, Robi; Sesmiarni, Zulfani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the basic concept of human resource management (HR) in the context of Islamic education applied in MDTA Sukma Illahi Canduang. HR management is an important component in improving the quality of educational institutions, including Madrasah Diniyah Takmiliyah Awaliyah (MDTA), because the success of the institution is greatly influenced by the quality and management of teaching and educational staff. This study uses a quantitative descriptive approach. With Population: All teaching and educational staff at MDTA Sukma Illahi Canduang with data collection techniques distributing the Islamic Education HR Questionnaire (Guttman Scale: Yes/No) and Data Analysis: Data were collected and analyzed by calculating the percentage of each